Comparison on performance of voltage sags miligation techniques - Norshafinash, Saudin; Noor Shahida, Jamoshid; Latifah, Mohamed; Mohd Aziz, Mohamed; N. M., Nayan; Ismail, Daut, Prof. Dr. (Universiti Teknologi MARA (UiTM), 2011)
Organized by Universiti Teknologi MARA, 3rd - 4th Jun 2009 at Concorde Hotel Shah Alam, Selangor, Malaysia.